Women’s Self Actualization in The Family (Moral Teaching in Serat Wulang Reh Putri) - Afif Syaiful Mahmudin (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The present life is a continuation of the past, the old cultural information will be an inspiration and knowledge in the future life, Javanese literature with its superiority is very relevant to be used to answer current problems. Especially in the case of women, the author is interested in bringing up a Javanese literary work by Paku Buwana X, entitled Serat Wulang Reh Putri. The research questions are: 1) Moral teachings in Serat Wulang Reh Putri for women in the family scope 2) The relevance of moral teachings in Serat Wulang Reh Putri for women in today's families. The researcher uses a qualitative approach with the type of library research study. The results of this study are: 1) The moral teachings in the Serat Wulang Reh Putri are the requirements and provisions for women who are getting married, the obligations of a wife in marriage, the prohibitions for women in the family and good behavior that must be done by women when they are married. married. 2) This fiber was originally intended for the daughter of the King or only for women in the palace, but because of its teachings, women in general can follow and implement it. Even though it was made centuries ago, the teachings contained in it are still very relevant to the current situation, especially for married women.